Current allocation policy is favorable for patients with hepatocellular carcinoma waiting for liver transplantation. Issue 12 (December 2018) - Ferre-Aracil, Carlos; Lledó, José-Luis; Aguilera, Lara; Garcia-Paredes, Ana; Rodríguez-Santiago, Enrique; Graus, Javier; García-González, Miguel; Nuño, Javier; López-Buenadicha, Adolfo; López-Hervás, Pedro; Rodríguez-Gandía, Miguel; Gea, Francisco; et al.
Abstract: Background: Patients with hepatocellular carcinoma (HCC) are a growing population of the transplantation waiting list (WL) for orthotopic liver transplantation (OLT). There is no consensus to prioritize these patients while on the WL. Aims: To assess whether patients with HCC were more prioritized than non-HCC patients based on their WL survival as primary outcome. Methods: Restrospective cohort study including patients listed for elective OLT from January 2013 to January 2016. Results: 165 patients with cirrhosis were listed for OLT: 64 in the HCC group (38.78%) and 101 in the non-HCC group (61.22%). Outcomes (HCC vs. non-HCC) were: OLT in 75.51% vs. 64.37%; death or dropout due to worsening in 20.41% vs. 27.59%, and delisting because of improvement in 4.08% vs. 8.05%. HCC patients had a significantly higher WL survival rate (HR = 0.45; 95% CI: 0.21–0.96); lower MELD score at transplantation (21 [20–24] vs. 24 [20–30]; p = 0.021); higher delta-MELD – the difference between MELD at transplantation and MELD at listing time – (3 [2–6] vs. 0 [0–5]; p = 0.024) and longer waiting time until OLT (143 [70–233] vs. 67 [21–164] days; p = 0.008). Conclusion: Despite having to wait longer, patients with HCC showed higher WL survival than non-HCC patients.